Cost of Measles Containment in an Ambulatory Pediatric Clinic. Issue 6 (June 2015) - Wendorf, Kristen A.; Kay, Meagan; Ortega-Sanchez, Ismael R.; Munn, Meaghan; Duchin, Jeffrey
<x xml:space="preserve">Abstract</x> Background: Measles is highly infectious; prompt containment of illnesses is necessary to prevent spread. In August 2013, a 13-year-old male with measles exposed patients and employees in a pediatric clinic. We studied containment costs to identify avoidable costs. Methods: Measles exposure was defined as in-person contact with or presence in the same room <2 hours after the measles patient. Costs were calculated retrospectively using published costs of measles–mumps–rubella vaccine, cost-to-charge ratios for inpatient care in urban Washington State and local emergency department charges for post-exposure immunoglobulin (IG). Personnel costs were calculated by multiplying hourly wages by time for employees who worked on the response; overhead was excluded. Results: Fifty-two patients, 60 caretakers and 10 employees were exposed. Personnel time cost $1961. Exposed patients had a mean age of 9.6 years (range: 2 months–19 years); 34 (65%) were fully vaccinated, and 18 (35%) were <12 months of age and too young to be vaccinated. Five patients (10%) were <6 months of age and required IG; 13 infants (25%) 6–11 months of age required measles–mumps–rubella vaccination. Caretakers followed up with their physicians for evidence of immunity. One employee had documented evidence of immunity; 9 required measles antibody testing or vaccination. Management of exposed persons cost $3694; overall clinic costs were $5655. Conclusion: Responding to 1 measles case cost the pediatric clinic more than $5000, despite isolating the patient promptly after examination. Documentation of employee immunity, vaccination of eligible patients and strict infection control precautions might reduce ambulatory costs associated with measles containment.